2021
DOI: 10.1016/j.eswa.2021.115141
|View full text |Cite
|
Sign up to set email alerts
|

Determination of COVID-19 pneumonia based on generalized convolutional neural network model from chest X-ray images

Abstract: X-ray units have become one of the most advantageous candidates for triaging the new Coronavirus disease COVID-19 infected patients thanks to its relatively low radiation dose, ease of access, practical, reduced prices, and quick imaging process. This research intended to develop a reliable convolutional-neural-network (CNN) model for the classification of COVID-19 from chest X-ray views. Moreover, it is aimed to prevent bias issues due to the database. Transfer learning-based CNN model was developed by using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(31 citation statements)
references
References 49 publications
0
20
0
Order By: Relevance
“…COVID-19 has been one of the strongest health problems in the last two years and is an area of interest not only in the medical area but also in machine learning. Classification algorithms, such as convolutional neural networks, have been widely used to provide a useful diagnosis to healthcare professionals [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39].…”
Section: Previous Workmentioning
confidence: 99%
“…COVID-19 has been one of the strongest health problems in the last two years and is an area of interest not only in the medical area but also in machine learning. Classification algorithms, such as convolutional neural networks, have been widely used to provide a useful diagnosis to healthcare professionals [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39].…”
Section: Previous Workmentioning
confidence: 99%
“…Moreover, a computer-aided diagnostic combined approach based on graph CNN and pre-trained CNN model (Kumar et al [19]), a deep Covix-net model (Vinod et al [20]), new deep hybrid and deep boosted hybrid learning models (Khan et al [21]), and a gradient weighted class activation mapping technique (Panwar et al [22]) for coronavirus detection exhibited accuracies of 97.60%, 97%, 98.53%, and 95%, respectively. Likewise, a DenseNet-201 architecture reported by Alhudhaif et al [23], a PSO-based eXtreme Gradient Boosting model recommended by Dias Júnior et al [24], an automatic AI-based system using majority voting ensemble techniques suggested by Chandra et al [25], and a bi-level prediction model by Das et al [26] exhibited respective accuracies of 94.96%,98.71%, 91.329%, and96.74%to diagnose COVID-19. Other novel techniques to detect coronavirus include a deep LSTM model (Demir et al [27]), Inception-v3 model based on deep CNN associated with Multi-Layered Perceptron model called CovScanNet (Sait et al [28]), and a hybrid deep CNN technique with discrete wavelet transform features (Mostafiz et al [29].…”
Section: Introductionmentioning
confidence: 99%
“…Scientists at the Centers for Disease Control (CDC) and World Health Organizations have identified common symptoms of this disease including dry cough, headache, difficulty breathing, weakness, and lack of smell and taste. Moreover, it has been found in some extreme cases, dyspnea and/or hypoxemia can occur a week after the appearance of the disease, accompanied by septic shock, acute respiratory distress syndrome (ARDS), and dysfunction of coagulation 6 . These different modes exacerbated the rapid spread of the virus and made it highly difficult to control the spread.…”
Section: Introductionmentioning
confidence: 99%